2023
DOI: 10.54103/2039-4942/18615
|View full text |Cite
|
Sign up to set email alerts
|

Calcareous Nannofossil Taxonomy and Biostratigraphy of the Toarcian-Lower Bajocian Colle Di Sogno Section (Lombardy Basin, Southern Alps, Italy)

Abstract: Calcareous nannofossil biostratigraphy was conducted in the Toarcian-lower Bajocian interval at Colle di Sogno (Lombardy Basin, Southern Alps, Northern Italy) where the type-section of the Sogno Formation consisting of pelagic marly limestone, marlstone and marly claystone was established. Semiquantitative analyses of calcareous nannofossil assemblages allowed to achieve a high-resolution biostratigraphy based on several biohorizons, including zonal/subzonal markers and additional events. The NJT5 to NJT9 Zone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 37 publications
(101 reference statements)
0
10
0
Order By: Relevance
“…Similar‐looking specimens have been documented in the Toarcian of Italy as Rucinolithus sp. by Casellato & Erba (2015), and demonstrated to represent isolated spines of Mitrolithus elegans in distal view in Sinemurian limestones of Iran by Abdi et al . (2022).…”
Section: Methodsmentioning
confidence: 96%
“…Similar‐looking specimens have been documented in the Toarcian of Italy as Rucinolithus sp. by Casellato & Erba (2015), and demonstrated to represent isolated spines of Mitrolithus elegans in distal view in Sinemurian limestones of Iran by Abdi et al . (2022).…”
Section: Methodsmentioning
confidence: 96%
“…Previous studies indicate that the LO of L. hauffii is either at the Callovian (Bown & Cooper, 1998; Mattioli & Erba, 1999; Young et al, 2022) or at the late Oxfordian stage, with the subject needing further investigation (Casellato, 2010). Considering these discrepancies in the biochronostratigraphic position of the LO of L. hauffii , we suggest further studies in the Lusitanian Basin to calibrate this event better.…”
Section: The Bathonian–early Callovian Agementioning
confidence: 99%
“…and Proarcestes sp. These species indicate the Illyrian (upper Anisian), Nevadites secedensis Zone (= Nevadites Zone of and Mietto et al 2003) (cf. Brack et al 2005Balini et al 2010;Jenks et al 2015) for the whole sampled part of the succession (see also Blendinger 1994, De Zanche et al 1995and Russo et al 2000 and confirm, as suggested by De Zanche et al (1995) and in contrast to Assereto (1969), the absence of the underlying Aploceras avisianum Subzone, Hungarites Zone sensu (= Reitzites reitzi Zone of Brack et al 2005) in the studied area.…”
Section: Marmoladamentioning
confidence: 99%
“…These species indicate the Illyrian (upper Anisian), Nevadites secedensis Zone (= Nevadites Zone of Mietto & Manfrin 1995 and Mietto et al . 2003) (cf. Brack et al .…”
Section: Geological Setting and Localitiesmentioning
confidence: 99%